The mental health and the work of endemic disease control agents in the covid-19 pandemic (Revista Contexto & Saúde, 2025)
This study aimed to investigate the occurrence of common mental disorders in Vector Control Workers (VCW) (Agentes de Combate à Endemias - ACE) in the state of Rio de Janeiro and the relationship with health and work conditions in the context of the COVID-19 pandemic. Methodology: This work used a cross-sectional study inspired by the Italian Workers' Model (MOI) and, therefore, with the participation of workers and unions in the category. Data collection was through a self-administered multidimensional questionnaire (online) that included the Self-Report Questionnaire (SRQ) for screening common mental disorders (CMD) from a sample of 139 participants. The statistical analysis used Pearson's chi-square and Fisher's exact tests. Results: We found that 43.2% of VCW had suspected CMD associated with gender (p ≤ 0.04), demand for mental health professionals (p ≤ 0.021), and different pre-pandemic complaints related to mental health (p ≤ 0.00). During the first months of the pandemic, more than 80% of VCW were working; 6.5% reported suicidal ideation and 15.8% depression. The research allowed actions to welcome and monitor workers in real-time and created a space for dialogues about mental health and work, especially during the pandemic. Conclusion: The research made it possible to identify the demands of VCW regarding mental health. Even though they are a predominantly male class, we observed important differences in the impact of the pandemic on the mental health of women and workers who had to work to combat COVID-19. Monitoring this population is essential because of their exposure to pesticides.
Keywords: worker health; mental disorders; vector control